Carbazole-linked porphyrin dimers for organic light emitting diodes: Synthesis and initial photophysical studies - SENGE, MATHIAS; RYAN, AOIFE; TUFFY, BRIAN; BLAU, WERNER (My University, 2011)
Carbazole linked porphyrin dimers were synthesized in good yields via stepwise Suzuki coupling reactions using bromoporphyrins and borylated carbazoles as the precursors, the latter of which were synthesized via known procedures from biphenyl derivatives. For comparative purposes porphyrin-carbazole monomers were synthesized. Single layer organic light emitting diodes (OLEDs) were created to demonstrate the optical properties of these materials. Light emission from these carbazole substituted porphyrins showed better results compared to previously examined bromo substituted porphyrins with better electroluminescence and lower turn-on voltages. Dimers exhibited turn-on voltages of 3V compared to 6V for monomeric porphyrin-carbazoles.
PUBLISHED
Keywords: Biochemistry; porphyrins; carbazoles